2012
DOI: 10.3109/00016489.2012.663933
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal trigeminal chemosensitivity in patients with postviral and post-traumatic olfactory dysfunction

Abstract: Patients with OD showed higher trigeminal thresholds than normal controls. Compared with controls, N1/P2 latencies of tERPs increased and amplitudes decreased in patients with OD. Older subjects showed longer latencies and lower amplitudes than young subjects in both controls and the OD group. Patients with PTOD exhibited worse psychophysical olfactory function and decreased trigeminal sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 23 publications
2
13
0
2
Order By: Relevance
“…A growing body of evidence also indicates that olfactory performance differences are not significant between older females and males (26)(27)(28) . This is consistent with the results of some other studies examining difference across life stages, that is, from prepubertal to elderly participants or from young to elderly adults, that found no significant gender differences (29)(30)(31)(32) .…”
Section: Introductionsupporting
confidence: 92%
“…A growing body of evidence also indicates that olfactory performance differences are not significant between older females and males (26)(27)(28) . This is consistent with the results of some other studies examining difference across life stages, that is, from prepubertal to elderly participants or from young to elderly adults, that found no significant gender differences (29)(30)(31)(32) .…”
Section: Introductionsupporting
confidence: 92%
“…Our results are in accordance with a recently published study by Parma et al [16], where the authors divided COVID-19 patients into 3 phenotypic clusters, with one of them having a loss of smell, taste, and chemesthesis. Although this phenomenon has been described in previous studies, it was rarely reported by the patients [17, 18]. The mechanisms are not clear and may be both peripheral and central.…”
Section: Discussionmentioning
confidence: 78%
“…An excellent example of this are the olfactory ERPs now widely used for assessment of olfactory functions, e.g. for medico-legal questions (Hummel et al, 2007, Ren et al, 2012. The method was developed by Kobal and Plattig, 1978, Plattig, 1989, Hummel and Kobal, 2001 In order to measure gustatory ERPs, the same prerequisites apply to the gustatory stimulator as they apply to olfactory stimulators.…”
Section: Q6mentioning
confidence: 98%